2021
DOI: 10.1002/jcp.30534
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of angiopoietin‐like proteins in inflammation: Mechanisms and potential as pharmacological targets

Abstract: Angiopoietin-like proteins (ANGPTLs), a family of eight secreted glycoproteins termed ANGTPL1-8, are involved in angiogenesis, lipid metabolism, cancer progression, and inflammation. Their roles in regulating lipid metabolism have been intensively studied, as some ANGPTLs are promising pharmacological targets for hypertriglyceridemia and associated cardiovascular disease. Recently, the emerging roles of ANGPTLs in inflammation have attracted great attention. First, elevated levels of multiple circulating ANGPT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 152 publications
0
16
0
Order By: Relevance
“…19,20 Recent studies have reported the role of ANGPTL8/betatrophin in nuclear factor-kappaB (NF-kappaB) mediated inflammation. [21][22][23] Thus the newly identified atypical member of ANGPTL family, ANGPTL8/betatrophin, may also be an inflammatory marker in insulin resistance and related diseases, which contributes to a better understanding of the role of ANGPTL8/ betatrophin in T2DM. But the mechanism of ANGPTL8/ betatrophin in regulating glucose metabolism remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Recent studies have reported the role of ANGPTL8/betatrophin in nuclear factor-kappaB (NF-kappaB) mediated inflammation. [21][22][23] Thus the newly identified atypical member of ANGPTL family, ANGPTL8/betatrophin, may also be an inflammatory marker in insulin resistance and related diseases, which contributes to a better understanding of the role of ANGPTL8/ betatrophin in T2DM. But the mechanism of ANGPTL8/ betatrophin in regulating glucose metabolism remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…ANGPTL-4 is a glycoprotein [25,26] that is involved in angiogenesis, lipid metabolism, and inflammation [27]. Particularly in CNS diseases, increased ANGPTL-4 reduces macrophage and microglia clearance of damaged myelin [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…The role of ANGPTL proteins in glucose and lipid metabolism and in cancer has been investigated intensively [ 86 , 87 , 88 ]. Certain ANGPTL proteins are promising pharmacological targets for hypertriglyceridemia [ 89 ], but the role of these proteins in ovine pregnancy toxemia requires further investigation.…”
Section: Lipid Metabolism-related Molecular Mechanisms In Pregnancy T...mentioning
confidence: 99%